Caprylate Salts Based on Amines as Volatile Corrosion Inhibitors for Metallic Zinc: Theoretical and Experimental Studies - Valente, Marco A. G.; Teixeira, Deiver A.; Azevedo, David L.; Feliciano, Gustavo T.; Benedetti, Assis V.; Fugivara, Cecílio S. (Frontiers in Chemistry, 2017)
The interaction of volatile corrosion inhibitors (VCI), caprylate salt derivatives from amines with zinc metallic surfaces is assessed by density functional theory (DFT) computer simulations, electrochemical impedance (EIS) measurements and humid chamber tests. The results obtained by the different methods were compared, and linear correlations were obtained between theoretical and experimental data. The correlations between experimental and theoretical results showed that the molecular size is the determining factor in the inhibition efficiency. The models used and experimental results indicated that dicyclohexylamine caprylate is the most efficient inhibitor.